Emirati Foreign Policy strategy in the Context of Ukraine-UAE Relations (Global Journal of Human-Social Science, 2022)
Abstract not found
Keywords: UAE; UKRAINE; regional power; foreign policy; strategy; relations; cooperation; transformation; interests